Persentage of Coral Cover and Megabenthos Diversity in â€œTanjung Jahaâ€, Tanjung Pulisan Waters, North Minahasa Regency - Daryanto, Adityas Andrew; Mamangkey, Noldy Gustaf; Manembu, Indri S; Boneka, Farnis B.; Sinjal, Cathrien A. L; Kambey, Alex D. (Sam Ratulangi University, 2021)
Tanjung Pulisan waters, especially the â€œTanjung Jahaâ€ are one of the diving tourism areas and have been designated as part of Likupang Special Economic Zone (SEZ), which has also been included in one of five super-priority tourist destinations in Indonesia. Based on the assumptions that tourism activities in the area would be very massive, it is presumed that the â€œPantai Kecilâ€ area will be affected by those activities. Therefore, this study aims to provide data on coral cover and megabenthic diversity, as a basis data for further research and or for policy decisions in the region. This study used the Benthos Belt Transect (BBT) method and the Underwater Photo Transect (UPT) method and they were analyzed with CPCE (Coral Point Count with Excel Extensions) and Microsoft Excel. The results showed that the percentage of coral cover in â€œTanjung Jahaâ€ was categorized as â€œGoodâ€ with a value of 55.92% which included 41.36% hard corals and 15.31% soft corals. At this location, 26 megabenthos were found which consisted of 5 different taxa and the diversity index was categorized as â€œMediumâ€ with the value of Hâ€™=1.36.Keywords: Â Â Â Coral Cover; Diversity; Pantai Kecil; Tanjung PulisanAbstrakPerairan Tanjung Pulisan, khususnya â€œTanjung Jahaâ€ merupakan salah satu daerah wisata penyelaman dan telah ditetapkan menjadi bagian dari Kawasan Ekonomi Khusus (KEK) Likupang dan juga masuk dalam salah satu dari lima destinasi wisata super prioritas di Indonesia. Dengan aktivitas pariwisata yang akan sangat masif, diperkirakan wilayah â€œTanjung Jahaâ€ akan terdampak oleh aktivitas pariwisata. Maka dari itu penelitian ini bertujuan untuk menyediakan data tutupan karang dan keanekaragaman megabentos, sebagai data awal sebagai informasi bagi riset selanjutnya maupun pada kebijakan yang akan berlaku di daerah tersebut. Penelitian ini menggunakan metode Benthos Belt Transect (BBT) dan metode Underwater Photo Transect (UPT) dengan analisa menggunakan CPCe (Coral Point Count with Excel extensions) dan Microsoft Excel. Hasil analisis menunjukan persentase tutupan karang di â€œTanjung Jahaâ€ terkategorikan â€œBaikâ€ dengan nilai 55.92% yang terdiri dari 41.36% karang keras dan 15.31% karang lunak. Di lokasi ini ditemukan 26 megabentos dari 5 taksa berbeda dengan indeks keanekaragaman terkategorikan â€œSedangâ€ dengan nilai Hâ€™=1.36.Kata kunci: Keanekaragaman; Pantai Kecil; Tutupan Karang; Tanjung Pulisan